Ubuntu : George M. Houser and the struggle for peace and freedom on two continents - Collins, Sheila D. (Ohio University Press, 2020)
"George M. Houser (1916-2015) was one of the most important civil rights and antiwar activists of the twentieth century. A draft resister during World War II who went to prison for his refusal to register for the draft, in 1942 Houser cofounded and led the Congress of Racial Equality (CORE), whose embrace of nonviolent protest strategies and tactics characterized the modern American Civil Rights Movement. Beginning in the 1950s, Houser played a critical role in pan-Africanist anti-colonial movements and his over thirty-year dedication to the cause of human rights and self-determination helped prepare the ground for the toppling of the South African apartheid regime. Throughout his life, Houser shunned publicity, preferring to let his actions speak his faith. Sheila Collins's well-researched biography recounts the events that informed Houser's life of activism--from his childhood experiences as the son of missionaries in the Philippines to his early grounding in the Social Gospel and the teachings of Mahatma Gandhi. In light of the corruption the U.S. and the world face today, Houser's story of faith and decisive action for human rights and social justice is one for our time"--